Index of Inclusive Education in the Bekasi City - Handayani, Sari; Sunardi, Sunardi (Journal of ICSAR, 2024)
The purpose of this research is to find out (1) how successful the implementation of inclusive education in Bekasi City, (2) how large the index of inclusive education achieved by inclusive elementary schools (SD) in Bekasi City, (3) what are the obstacles faced in implementing inclusive education in Bekasi city. The inclusion index is obtained by conducting a survey on the coordinators of inclusiveness using 45 indicators developed from the dimensions of creating an inclusive culture, producing inclusive policies, and developing inclusive education. This research was conducted at eight inclusive schools in Bekasi City. The results showed that the average inclusion index in Bekasi City was 8. The smallest index in schools was 7 and the largest index reached 9. The dimension of inclusion index to create an inclusive culture was 8. The dimension of inclusion index was 9 to produce inclusive policies and the dimension of inclusion index to the development of education inclusive of 8. Overall all dimensions are in the good category. However, there are two indicators on the dimension of creating an inclusive culture and one indicator on the dimension of developing inclusive education which is still lacking.